"Does Pakistan still have polio cases?": Exploring discussions on polio and polio vaccine in online news comments in Pakistan. Issue 3 (15th January 2021) - Ittefaq, Muhammad; Baines, Annalise; Abwao, Mauryne; Shah, Sayyed Fawad Ali; Ramzan, Tayyab
Highlights: Polio is considered a serious threat to public health in Pakistan. Online commenters show empathy for polio health care workers. Misinformation on polio vaccine as an amplification of new polio cases. Online commenters correct misinformation and false claims by providing factual information on polio. Pakistan launches the Perception Management Initiative (PMI) to block anti-vaccination propaganda social media pages. Abstract: Introduction: Polio, which is caused by poliovirus, is a contagious, potentially crippling, and deadly disease. Pakistan is one of the countries in which polio is still endemic in the 21st century. In 2019, 146 polio cases were reported across the country with some resulting in deaths. Following the spread of rumors insinuating that children were falling sick after receiving an anti-polio vaccine, a mob attacked and set fire to a small hospital in the Peshawar district in April 2019. The present study investigates readers' discussions that emerged from Dawn's online readers' comments on polio-related news stories in Pakistan. Methods: Using thematic analysis, we analyzed ( N = 2216) comments made by readers in the polio-related news stories published on Dawn.com from January 1, 2012, to March 1, 2020. Results: Seven major themes emerged from the analysis of the comments: 1) reasons for and challenges resulting in the failure to eradicate polio; 2) proposed solutions and policy changes to eradicate polio; 3) misinformation; 4) criticism, frustration, and shame; 5) comparison of Pakistan to other countries; 6) the internet as a public sphere; 7) suffering, empathy, and appreciation. Overall, our findings suggested that commenters are knowledgeable about polio vaccines and consider polio a serious threat to public health in Pakistan . Conclusion: Our study not only validated previous study findings such as reasons, challenges, and issues related to polio vaccination, but also found new challenges in online news sites concerning misinformation on polio and polio vaccination in Pakistan.